Formula apportionment: Factor allocation and tax avoidance - Sebastian Eichfelder; Frank Hechtner; Jochen Hundsdoerfer (Arbeitskreis Quantitative Steuerlehre (arqus), 2017)
This paper addresses the question of how firms react to tax incentives in a formula apportionment (FA) tax regime. Under FA, the profits of all consolidated entities of a business group are summed and then allocated according to a formula based on FA factors. We hypothesize that firms may change the allocation of real production factors and/or manipulate the FA factor through tax avoidance strategies. Analysing FA tax effects of the German local business tax with payroll expense as the exclusive FA factor, we find empirical evidence consistent with both hypotheses. Regarding the allocation of production factors, we observe significant tax effects on labour input at the intensive margin but not on labour input at the extensive margin. In addition, we find evidence of an indirect FA spillover effect on capital investment. Our findings on tax avoidance proxies are consistent with tax-induced manipulations of payroll expense as an FA factor to save tax payments.
Keywords: H32; H71; H73; J61; 330; Factor Allocation; Formula Apportionment; Profit Shifting; Tax Avoidance